Barley strigolactone signalling mutant hvd14.d reveals the role of strigolactones in abscisic acid‐dependent response to drought. (22nd July 2020) - Marzec, Marek; Daszkowska‐Golec, Agata; Collin, Anna; Melzer, Michael; Eggert, Kai; Szarejko, Iwona
Abstract: Strigolactones (SLs) are a group of plant hormones involved in many aspects of plant development and stress adaptation. Here, we investigated the drought response of a barley ( Hordeum vulgare L.) mutant carrying a missense mutation in the gene encoding the SL‐specific receptor HvD14. Our results clearly showed that hvd14.d mutant is hyper‐sensitive to drought stress. This was illustrated by a lower leaf relative water content (RWC), impaired photosynthesis, disorganization of chloroplast structure, altered stomatal density and slower closure of stomata in response to drought in the mutant compared to the wild type parent cultivar Sebastian. Although the content of abscisic acid (ABA) and its derivatives remained unchanged in the mutant, significant differences in expression of genes related to ABA biosynthesis were observed. Moreover, hvd14.d was insensitive to ABA during seed germination. Analysis of Arabidopsis thaliana mutant atd14‐1 also demonstrated that mutation in the SL receptor resulted in increased sensitivity to drought. Our results indicate that the drought‐sensitive phenotype of barley SL mutant might be caused by a disturbed ABA metabolism and/or signalling pathways. These results together uncovered a link between SL signalling and ABA‐dependent drought stress response in barley. Abstract : Barley line with a mutation in the gene encoding the strigolactone (SL)‐specific receptor D14 are sensitive to drought stress and less sensitive to abscisic acid (ABA). The drought‐intolerant and ABA‐insensitive phenotype during germination of the barley SL mutant might be caused by a not efficient ABA signal transduction pathway.